The Major Peanut Allergen Ara h 2 Produced in Nicotiana benthamiana Contains Hydroxyprolines and Is a Viable Alternative to the E. Coli Product in Allergy Diagnosis - Üzülmez, Öykü; Kalic, Tanja; Mayr, Vanessa; Lengger, Nina; Tscheppe, Angelika; Radauer, Christian; Hafner, Christine; Hemmer, Wolfgang; Breiteneder, Heimo (Frontiers in Plant Science, 2021)
Peanut allergy is a potentially life-threatening disease that is mediated by allergen-specific immunoglobulin E (IgE) antibodies. The major peanut allergen Ara h 2, a 2S albumin seed storage protein, is one of the most dangerous and potent plant allergens. Ara h 2 is post-translationally modified to harbor four disulfide bridges and three hydroxyprolines. These hydroxyproline residues are required for optimal IgE-binding to the DPYSPOHS motifs representing an immunodominant IgE epitope. So far, recombinant Ara h 2 has been produced in Escherichia coli, Lactococcus lactis, Trichoplusia ni insect cell, and Chlamydomonas reinhardtii chloroplast expression systems which were all incapable of proline hydroxylation. However, molecular diagnosis of peanut allergy is performed using either natural or E. coli-produced major peanut allergens. As the majority of patients’ IgE is directed to Ara h 2, it is of great importance that the recombinant Ara h 2 harbors all of its eukaryotic post-translational modifications. In this study, we produced hydroxyproline-containing and correctly folded Ara h 2 in the endoplasmic reticulum of leaf cells of Nicotiana benthamiana plants using the plant virus-based magnICON® transient expression system with a yield of 200 mg/kg fresh biomass. To compare prokaryotic to eukaryotic expression methods, Ara h 2 was expressed in E. coli together with the disulfide-bond isomerase DsbC and thus harbored disulfide bridges but no hydroxyprolines. The recombinant allergens from N. benthamiana and E. coli were characterized and compared to the natural Ara h 2 isolated from roasted peanuts. Natural Ara h 2 outperformed both recombinant proteins in IgE-binding and activation of basophils via IgE-crosslinking, the latter indicating the allergen’s potency. Interestingly, significantly more efficient IgE-crosslinking by the N. benthamiana-produced allergen was observed in comparison to the one induced by the E. coli product. Ara h 2 from N. benthamiana plants displayed a higher similarity to the natural allergen in terms of basophil activation due to the presence of hydroxyproline residues, supporting so far published data on their contribution to the immunodominant IgE epitope. Our study advocates the use of N. benthamiana plants instead of prokaryotic expression hosts for the production of the major peanut allergen Ara h 2.